Anti-inflammatory activity of aqueous extract and bioactive compounds identified from the fruits of Hancornia speciosa Gomes (Apocynaceae). Issue 1 (December 2016) - Torres-Rêgo, Manoela; Furtado, Allanny; Bitencourt, Mariana; Lima, Maira; Andrade, Rafael; Azevedo, Eduardo; Soares, Thaciane da Cunha; Tomaz, José; Lopes, Norberto; da Silva-Júnior, Arnóbio; Zucolotto, Silvana; Fernandes-Pedrosa, Matheus de Freitas
Abstract Background Hancornia speciosa Gomes (Apocynaceae), popularly known as "mangabeira, " has been used in folk medicine to treat inflammatory disorders, hypertension, dermatitis, diabetes, liver diseases and gastric disorders. Although the ethnobotany indicates that its fruits can be used for the treatment of ulcers and inflammatory disorders, only few studies have been conducted to prove such biological activities. This study investigated the anti-inflammatory properties of the aqueous extract of the fruits ofH. speciosa Gomes as well as its bioactive compounds using in vivo experimental models. Methods The bioactive compounds were identified by High Performance Liquid Chromatography coupled with diode array detector (HPLC-DAD) and Liquid Chromatography coupled with Mass Spectrometry (LC-MS). The anti-inflammatory properties were investigated through in vivo tests, which comprised xylene-induced ear edema, carrageenan-induced peritonitis and zymosan-induced air pouch. The levels of IL-1β, IL-6, IL-12 and TNF-α were determined using ELISA. Results Rutin and chlorogenic acid were identified in the extract as the main secondary metabolites. In addition, the extract as well as rutin and chlorogenic acid significantly inhibited the xilol-induced ear edema and also reduced the cell migration in both carrageenan-induced peritonitis and zymosan-induced air pouch models. Reduced levels of cytokines were also observed. Conclusion This is the first study that demonstrated the anti-inflammatory activity of the extract ofH. speciosa fruits against different inflammatory agents in animal models, suggesting that its bioactive molecules, especially rutin and chlorogenic acid are, at least in part, responsible for such activity. These findings support the widespread use ofHancornia speciosa in popular medicine and demonstrate that its aqueous extract has therapeutical potential for the development of herbal drugs with anti-inflammatory properties.